Bone mineral density in adolescent elite ballet dancers - Wielandt, T.; van den Wyngaert, T.; Uijttewaal, J. R.; Huyghe, I.; Maes, M.; Stassijns, G. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Data documenting BMD in pre-professional adolescent ballet dancers is limited. This cross-sectional study assesses bone mineral density (BMD) in young adolescent elite ballet dancers and compares BMD values between males and females (with and without normal menarche) and body composition between dancers with and without low Z-score. METHODS: Cross-sectional study of third year ballet students (female=23; male=15; mean age 14.7 years; SD: 0.5) of The Royal Ballet School of Antwerp (Belgium) training 22 hours a week. They completed questionnaires and underwent dual energy X-ray absorptiometry (DXA) to measure BMD and body composition. Each female participant completed questionnaires assessing menstrual status. RESULTS: DXA revealed that 12 out of 38 (32%) of the dancers had Z-score <-1. On average, male dancers had a lower BMD compared to an age-matched reference population (mean Z-score -0.9; SD 0.5), with 7 out of 15 having Z-score <-1. Overall, absolute BMD values were highest in the legs, followed by spine and arms. Dancers with Z-score <-1 had a significantly lower total mass. 43% of female ballet dancers had not yet had their first period and 39% had oligomenorrhea, but no significant differences between groups was detected. CONCLUSIONS: A third of adolescent elite ballet dancers had low to very low Z-score. Nearly 2 out of 3 dancers with a Z-score <-1 were males, showing that low BMD is not limited to female dancers. Among female dancers menstrual dysfunction was frequent, without apparent impact on BMD or body composition in the studied age group.